1999
DOI: 10.1046/j.1365-2958.1999.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Type IV pili of pathogenic Neisseriae elicit cortical plaque formation in epithelial cells

Abstract: SummaryThe pathogenic Neisseriae Neisseria meningitidis and Neisseria gonorrhoeae, initiate colonization by attaching to host cells using type IV pili. Subsequent adhesive interactions are mediated through the binding of other bacterial adhesins, in particular the Opa family of outer membrane proteins. Here, we have shown that pilus-mediated adhesion to host cells by either meningococci or gonococci triggers the rapid, localized formation of dramatic cortical plaques in host epithelial cells. Cortical plaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
210
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(220 citation statements)
references
References 92 publications
6
210
3
1
Order By: Relevance
“…The A431 human epidermoid carcinoma cell line (a kind gift of S. Schmid) was used for these studies. These cells have been used previously for neisseria infection studies and their maintenance has been described (Larson et al, 2002;Merz et al, 1999). Briefly, cells were maintained in Dulbecco's Modified Eagle's Medium (DMEM; Mediatech) supplemented with 10 % heat-inactivated fetal bovine serum (FBS; Gibco), and incubated at 37 uC, 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The A431 human epidermoid carcinoma cell line (a kind gift of S. Schmid) was used for these studies. These cells have been used previously for neisseria infection studies and their maintenance has been described (Larson et al, 2002;Merz et al, 1999). Briefly, cells were maintained in Dulbecco's Modified Eagle's Medium (DMEM; Mediatech) supplemented with 10 % heat-inactivated fetal bovine serum (FBS; Gibco), and incubated at 37 uC, 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Tfp retraction recruits host cell components to the cortex beneath adhered microcolonies. These cortical plaques are enriched in cytoskeletal and signalling proteins (Edwards et al, 2000;Lee et al, 2005;Merz et al, 1999;Weyand et al, 2006), some of which have been shown to play a role in invasion (Lee et al, 2005;Shaw & Falkow, 1988). The relationship between the cortical plaque and the microcolony is dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…CD46 may transduce a signal to the cell via its cytoplasmic tail. Indeed, in a recent study, neisserial type IV pili were reported to be required for cortical plaque formation in epithelial cells (Merz et al, 1999). These plaques are enriched in cellular components involved in bacterial adhesion to target cells such as phosphotyrosine, actin and ezrin (Merz and So, 1997;Merz et al, 1999).…”
mentioning
confidence: 99%
“…Indeed, in a recent study, neisserial type IV pili were reported to be required for cortical plaque formation in epithelial cells (Merz et al, 1999). These plaques are enriched in cellular components involved in bacterial adhesion to target cells such as phosphotyrosine, actin and ezrin (Merz and So, 1997;Merz et al, 1999). Once intimate adhesion is achieved, the surfaces of heavily infected cells appear to be denuded of microvilli (Merz and So, 1997;Deghmane et al, 2000).…”
mentioning
confidence: 99%
“…Mais il ne faut pas oublier que les humaines. Nombre de modifications des cellules humaines associées à l'infection par Neisseria ne se font plus [7,8]. L'expression génique des cellules humaines en réponse à l'infection est aussi fortement modifiée en présence ou en l'absence de force mécanique [9].…”
Section: Spiderman Microscopiqueunclassified